A Near Miss: Case Report and Literature Review - Alsufayan Fahad; Mohamed Adam Omar (Thieme Medical Publishers, Inc., 2012)
We report a 28-week gestation premature infant with rare complication of endotracheal intubation. A piece from the plastic sheath of the stylet was retrieved inside the endotracheal tube after extubation.